The Right of Children to Participate: Scopes and Challenges for Social Research - Saracostti, Mahia; Caro, Pamela; Grau, María O.; Kinkead, Ana Patricia; Vatter, Nicolás (Revista del CLAD Reforma y Democracia, 2015)
In 1989 the UN General Assembly adopts the Convention on the Rights of Children and Adolescents (CRC) recognizing children and adolescents as subjects of rights. To be mandatory, its ratification involves creating conditions for children and adolescents to express themselves and be considerate. This means that their voice must be included in the scientific work, not as a complement or contrast, but as an actor priority, especially in public policies that compete. This work aims to contribute to the development of productions to consider the participation of children and adolescents, through the approach of challenges and scope for research analysis focusing on three areas: the role of the State, families and the extent of child participation. The paper is organized in compliance with two objectives. First, to describe the theoretical bases that support the right of participation of children and adolescents, checking the CRC and the Model of Integral Protection of Children; the CRC and the right of participation; and the approach to child participation in research in relevant areas. And second, to characterize empirical research involving children and adolescents conducted in various contexts since 1998. We conclude that the speech of the CRC has faced in practice with traditional conceptions about the role of children and adolescents, both in macro scenarios (politics and State) as well as microsocial scenarios (the family), “crashing” with traditional prevailing approaches (guardian). The lack of understanding of the meaning of participation and the resistance to change of the place of childhood acts as barriers to the installation of studied law, prevailing form of action mediated by adult link. By contrast, the concept of scaffolding will allow a shift in the promotion of citizenship and children’s role and its forms of observation, challenging us to investigate the childhood experience from promotion (not from deficiencies), independent of particular features incorporating the concepts of agency, equity and governance.